Meningkatkan Pemahaman terhadap Agresif Berkendara pada Remaja Desa Sukamukti - Firda Putri Nurita; Ninik Paryati; Setyo Supratno (Masyarakat Mandiri : Jurnal Pengabdian dan Pembangunan Lokal, 2024)
Aggressive driving is driving under the influence of emotional instability that has a risky impact on others. Aggressive driving behavior occurs when drivers have difficulty controlling their emotions while they are driving. Adolescence is a time of searching for identity, therefore adolescents often show forms of aggressive behavior, one of which is driving aggressively. This community service program aims to increase understanding and awareness of driving and stabilizing emotions when driving using electric bicycles for students in one of the classes in Sukamukti Village, Bojongmangu. This activity was attended by 33 students in grade 6 MI. The research method used community education by means of observation and socialization with the homeroom teacher of grade 6 MI, through three stages, namely, pre-test, psychoeducation, and evaluation in the form of a post-test. There are final results, namely, before conducting psychoeducation, the understanding was 0% and after psychoeducation, the percentage was 18%, there was an increase of 18%.